Familial discrepancy of clinical outcomes associated with fibrinogen Dorfen: A case of huge genital hematoma after episiotomy. Issue 6 (23rd March 2016) - Kagami, Kyosuke; Yamazaki, Rena; Minami, Tetsuya; Okumura, Nobuo; Morishita, Eriko; Fujiwara, Hiroshi
Abstract: This study demonstrates a case of a huge genital hematoma after delivery, associated with fibrinogen Dorfen. Fibrinogen Dorfen is the mutation of a fibrinogen‐coded exon gene, which has a single heterozygous GCC → GTC transition at codon 289 of the γ gene, predicting an Ala → Val substitution. Because Ala289 plays a crucial role in maintaining the structure of the polymerization site of hole 'a' via a hydrogen bond, it is speculated that the γ 289Ala → Val substitution can change not only the fibrinogen structure, but also the function of polymerization. In our case, although the patient's gene mutation was the same as that of her mother, there was a discrepancy in the clinical outcomes. Although the precise mechanism regarding this discrepancy remains unknown, it may cause different perinatal outcomes in terms of vaginal delivery, such as the severe bleeding in this patient and the absence of clinical symptoms in her mother. This is the first report suggesting the heterogeneity of fibrinogen functions of fibrinogen Dorfen, which may be critical to the clinical outcome.